INOVASI PELAYANAN SIRKULASI OPEN LIBRARY TELKOM UNIVERSITY SAAT COVID-19 - Salsabila Anjani; Sukaesih Sukaesih; Evi Nursanti Rukmana; Samson CMS (Nusantara Journal of Information and Library Studies (N-JILS), 2021)
Libraries in the face of the Covid-19 pandemic have limited library service activities. Telkom University Open Library as a university library makes various efforts and innovations during the pandemic to continue to provide services to its users. The purpose of this article is to find out how to innovate Telkom University Open Library circulation services during Covid-19. The research method uses a descriptive qualitative approach, through data collection techniques of observation, interviews, and literature review. Interviews were conducted virtually with the Head of Administration Service for the Open Library Telkom University. The results of this study Open Library Telkom University has made innovations that help users to be able to access information sources both on-site and online. Circulation services at the Telkom University Open Library have been reopened, but still, apply the applicable health protocols. Innovations made include making reservations before coming directly to the place to avoid crowds. Then the provision of electronic book access services, borrowing and returning books through online transportation services, and paying late returns with a digital wallet. Finally, the innovations carried out by Telkom University's Open Library during the pandemic provide easy access to library materials for its users.Keyword: service innovation; Covid-19; Telkom University Open LibraryABSTRAKPerpustakaan dalam menghadapi pandemi Covid-19 membatasi kegiatan pelayanan perpustakaan. Open Library Telkom University sebagai perpustakaan perguruan tinggi melakukan berbagai upaya dan inovasi di masa pandemi untuk tetap memberikan pelayanan kepada pemustakanya. Tujuan artikel ini untuk mengetahui bagaimana inovasi pelayanan sirkulasi Open Library Telkom University saat Covid-19. Metode penelitian menggunakan deskriptif melalui pendekatan kualitatif, melalui teknik pengumpulan data observasi, wawancara, dan kajian literatur. Wawancara dilakukan secara virtual dengan Kepala Urusan Administrasi Pelayanan Open Library Telkom University. Hasil dari penelitian ini Open Library Telkom University telah melakukan inovasi yang membantu pemustaka untuk dapat mengakses sumber informasi baik secara on-site maupun online. Pelayanan sirkulasi di tempat Open Library Telkom University sudah dibuka kembali, namun tetap dengan menerapkan protokol kesehatan yang berlaku. Inovasi yang dilakukan antara lain, melakukan reservasi sebelum datang langsung ke tempat demi menghindari terjadinya kerumunan. Kemudian disediakannya pelayanan akses buku elektronik, pelayanan peminjaman dan pengembalian buku melalui jasa transportasi online, dan pembayaran denda keterlambatan pengembalian dengan dompet digital. Akhir kata, inovasi yang dilakukan Open Library Telkom University di masa pandemi memberikan kemudahan akses bahan pustaka bagi pemustakanya.